Controlled Formation of α- and β-Bi2O3 with Tunable Morphologies for Visible-Light-Driven Photocatalysis - Thomas Cadenbach; María Isabel Loyola-Plúa; Freddy Quijano Carrasco; Maria J. Benitez; Alexis Debut; Karla Vizuete (Molecules)
Water pollution caused by increasing industrial and human activity remains a serious environmental challenge, especially due to the persistence of organic contaminants in aquatic systems. Photocatalysis offers a promising and eco-friendly solution, but in the case of bismuth oxide (Bi2O3) there is still a limited understanding of how structural and morphological features influence photocatalytic performance. In this work, a straightforward hydrothermal synthesis method followed by controlled calcination was developed to produce phase-pure α- and β-Bi2O3 with tunable morphologies. By varying the hydrothermal temperature and reaction time, distinct structures were successfully obtained, including flower-like, broccoli-like, and fused morphologies. XRD analyses showed that the final crystal phase depends solely on the calcination temperature, with β-Bi2O3 forming at 350 °C and α-Bi2O3 at 500 °C. SEM and BET analyses confirmed that morphology and surface area are strongly influenced by the hydrothermal conditions, with the flower-like β-Bi2O3 exhibiting the highest surface area. UV–Vis spectroscopy revealed that β-Bi2O3 also has a lower bandgap than its α counterpart, making it more responsive to visible light. Photocatalytic tests using Rhodamine B showed that the flower-like β-Bi2O3 achieved the highest degradation efficiency (81% in 4 h). Kinetic analysis followed pseudo-first-order behavior, and radical scavenging experiments identified hydroxyl radicals, superoxide radicals, and holes as key active species. The catalyst also demonstrated excellent stability and reusability. Additionally, Methyl Orange (MO), a more stable and persistent azo dye, was selected as a second model pollutant. The flower-like β-Bi2O3 catalyst achieved 73% degradation of MO at pH = 7 and complete removal under acidic conditions (pH = 2) in less than 3 h. These findings underscore the importance of both phase and morphology in designing high-performance Bi2O3 photocatalysts for environmental remediation.